Factors affecting sporulation and infection of Peronospora sparsa in New Zealand boysenberry gardens - Mudiyanselage, Anusara M.H.; Ridgway, Hayley J.; Walter, Monika; Smith, Jason; Jaspers, Marlene V.; Jones, E. Eirian (New Zealand Plant Protection, 2021)
Downy mildew, caused by Peronospora sparsa, is an economically important disease of boysenberries. Sporangia produced on infected tissue initiate berry infections; however the timing of sporangial release under New Zealand environmental conditions is unknown. The number of P. sparsa sporangia trapped on Vaseline®-coated slides placed weekly in three boysenberry gardens in the Nelson region from October to December in 2010 and September to December in 2011 was determined. Climate data were used to determine environmental factors that promoted sporangia production/release. Incidence of dryberry symptoms and sporulation on tissue samples incubated at 15 or 20°C under high relative humidity (RH) were assessed. Peronospora sparsa sporangia were observed on slides from all three sites, with peak sporangial numbers in mid-November in both years. Sites with the highest numbers of sporangia trapped in November had higher dryberry incidence in December. Data indicated that sporangial release was triggered by percentage of rainy days, RH and warm temperatures (16–23°C) in early spring, where high moisture periods promoted sporulation and a subsequent dry period allowed sporangial release. This study improves understanding of the timing of sporangial release to inform management practices.